Comparative Assessment of Nuclear and Nucleolar Cytochemical Parameters of Oral Epithelial Cells in Smokers and Non-Smokers by Methyl Green-Pyronin Staining - Shahrzad Adhami; Hamid Ejtehadi; Jahanshah Salehinejad; Nooshin Mohtasham; Nasser Mahdavi-Shahri; Mahdi Pazouki (Mashhad University of Medical Sciences, 2012)
Introduction: A strong relationship exists between cigarette smoking and the development of oral squamous cell carcinoma. Smoking can significantly increase cellular proliferation. Nevertheless, there is little reference in literature to the cytological assessment of oral mucosa in this respect. Methods: Changes in nuclear and neucleolar cytomorphometric parameters such as diameter, surface, number and color intensity, in cytologic smears which were collected from normal buccal mucosa of 30 cigarette smokers and 30 non smokers, using methyl green-pyronin staining were studied. Results: Our findings attested to smoking as significant inductive factor in cytochemistry as well as morphologic changes. Conclusion: This technique is a valuable tool.